Pertussis: Biology, epidemiology and prevention. Issue 48 (21st November 2016) - Saadatian-Elahi, Mitra; Plotkin, Stanley; Mills, Kingston H.G.; Halperin, Scott A.; McIntyre, Peter B.; Picot, Valentina; Louis, Jacques; Johnson, David R.
Highlights: B. pertussis still continues to circulate in the human population. Better control of pertussis can be achieved by: Broadening of vaccination strategies (e.g. pregnant women, neonates). Improving vaccination practice (e.g. on-time adherence to vaccination schedules). Development of new highly immunogenic and efficacious pertussis vaccines. Human challenge studies are a way forward to study infection and vaccination. Abstract: Despite long-standing vaccination programs, substantial increases in reported cases of pertussis have been described in several countries during the last 5 years. Cases among very young infants who are at greatest risk of pertussis-related hospitalizations and mortality are the most alarming. Multiple hypotheses including but not limited to the availability of more sensitive diagnostic tests, greater awareness, and waning vaccine-induced immunity over time have been posited for the current challenges with pertussis. The conference "Pertussis: biology, epidemiology and prevention" held in Annecy-France (November 11–13, 2015) brought together experts and interested individuals to examine these issues and to formulate recommendations for optimal use of current vaccines, with a particular focus on strategies to minimize severe morbidity and mortality among infants during the first months of life. The expert panel concluded that improving vaccination strategies with current vaccines and development of new highly immunogenic and efficacious pertussis vaccines that have acceptable adverse event profiles are currently the two main areas of investigation for the control of pertussis. Some possible pathways forward to address these main challenges are discussed in this report.